PENGARUH BUDAYA ORGANISASI, KOMITMEN, DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA GURU PAUD KECAMATAN KRAMAT JATI, JAKARTA TIMUR - Mudzalifah; Yulita Pujilestari; R. Dede Siswandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effects of organizational culture, commitment, and work motivation on the work productivity of early childhood education (PAUD) teachers in Kramat Jati District, East Jakarta, both partially and simultaneously. The study employed a quantitative approach using a survey method with an associative research design. The population consisted of 295 teachers from 62 PAUD institutions, with a sample of 170 respondents determined using the Slovin formula and a proportional random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression and multiple linear regression with the assistance of IBM SPSS Statistics. The results revealed that organizational culture had a positive and significant effect on teachers' work productivity, with a correlation coefficient of 0.824 and a coefficient of determination of 67.8%. Commitment also had a positive and significant effect on teachers' work productivity, with a correlation coefficient of 0.794 and a coefficient of determination of 63.0%. Furthermore, work motivation had a positive and significant effect on teachers' work productivity, with a correlation coefficient of 0.758 and a coefficient of determination of 57.5%. Simultaneously, organizational culture, commitment, and work motivation had a positive and significant effect on teachers' work productivity, with a multiple correlation coefficient of 0.850 and a coefficient of determination of 72.2%. The findings indicate that organizational culture is the most dominant factor influencing teachers' work productivity, followed by commitment and work motivation. Therefore, strengthening organizational culture, enhancing teachers' commitment, and fostering sustainable work motivation are essential strategies for improving teachers' work productivity.